The Influence of Internal Factors on the Success of Leprosy Treatment at Cibuaya Health Center, Indonesia - Sari, Anggi Novita; Risman, Muhammad; Affandi, Thysa Thysmelia (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Indonesia still has a significant number of leprosy cases; there was an increase in cases to 12,441 compared to the previous year, which was 10,976 (WHO, 2023). At the national level, the target percentage of leprosy treatment has not been reached; 87% achievement was obtained, while the national indicator target is 90%. Age, gender, marital status, education level, occupation, and leprosy type are among the internal characteristics that contribute to the effectiveness of leprosy therapy. The most leprosy cases in Karawang Regency are found in Cibuaya Health Center, Indonesia. Aims: This study aims to determine the influence of internal factors (age, gender, marital status, education, occupation, and leprosy type) on the success of leprosy treatment at the Cibuaya Health Center. Methods: Observational analysis with cross-sectional design was used in this study with a sample size of 110 respondents at the Cibuaya Health Center. Medical records from patients receiving leprosy treatment at the Cibuaya Health Center served as the sample. Total sampling, a non-probability sampling technique, has been used. The study was conducted in June 2024. Results: Leprosy treatment success was found to be influenced by age (p=0.09), gender (p=0.001), marital status (p=0.012), education level (p=0.001), and leprosy type (p=0.001) in the bivariate analysis using the Chi-square test. However, the occupation factor did not show a significant effect on treatment success (p=0.275). Based on multivariate logistic regression analysis, Leprosy type was the most dominant factor influencing treatment success (Exp(B) = 38.863). The limitation of this study is that it did not investigate internal factors in the success of leprosy treatment by using laboratory results (such as BTA testing) after treatment. Conclusion: The success of leprosy treatment at the Cibuaya Health Center is influenced by age, gender, marital status, education level, and leprosy type. The most influential factor on the success of leprosy treatment is the type of leprosy. However, the occupation factor did not show a significant effect on treatment success. These findings can inform targeted strategies to improve treatment outcomes, especially among high-risk groups such as Multibacillary (MB) patients and the elderly.